2017
DOI: 10.1111/ijag.12322
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate content affects structure and bioactivity of sol‐gel silicate bioactive glasses

Abstract: Bioactive glasses can heal bone defects and bond with bone through formation of hydroxyl carbonate apatite (HCA) surface layer. Sol-gel derived bioactive glasses are thought to have potential for improving bone regeneration rates over melt-derived compositions. The 58S sol-gel composition (60 mol% SiO2, 36 mol% CaO, and 4 mol% P2O5) has appeared in commercial products. Here, hydroxyapatite (HA) was found to form within the 58S glass during sol-gel synthesis after thermal stabilization. The preformed HA may lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…The samples with lower network connectivity are likely to be more reactive upon immersion in SBF in comparison to the other glasses, since the lower network connectivity means a greater population of NBOs to disrupt the silica network, leading to an easier dissolution of glass components. Conversely, increasing the network connectivity increases the chemical durability of the whole structure …”
Section: Resultsmentioning
confidence: 99%
“…The samples with lower network connectivity are likely to be more reactive upon immersion in SBF in comparison to the other glasses, since the lower network connectivity means a greater population of NBOs to disrupt the silica network, leading to an easier dissolution of glass components. Conversely, increasing the network connectivity increases the chemical durability of the whole structure …”
Section: Resultsmentioning
confidence: 99%
“…The final ADA precipitate was lyophilized and its structure was assessed by FTIR and solid‐state nuclear magnetic resonance (NMR). Besides, its aldehyde group content and oxidation degree were also determined according to the previous methods …”
Section: Methodsmentioning
confidence: 99%
“…Bioactive glass powders of 60 mol% SiO 2 , 12 mol% P 2 O 5 and 28 mol% CaO composition were prepared through solgel processing route as previously described by Ting et al [21]. All reagents were purchased from Sigma-Aldrich (Dorset, UK).…”
Section: Powder Synthesismentioning
confidence: 99%
“…For this reason BG of various compositions prepared by sol-gel method are often preconditioned prior to cell culture [20]. Recent studies showed that increasing the phosphate content in the sol-gel glass led to formation of a phosphate glass network, which co-exists with the silicate network [21]. Dissolution studies in simulated body fluid (SBF) showed the pH remained neutral but phosphate (apatite) deposition still occurred within 24 h. Therefore, it is hypothesized that the incorporation of phosphate into glass network not only would be an important attributing factor in stabilizing the local pH but also avoids the need for a preconditioning step.…”
Section: Introductionmentioning
confidence: 99%